Track substructure assessment using non-destructive load tests. A Portuguese case study. - Chiara, F. (2012)
Comfort and safety are crucial aspects in a transport infrastructure project. Depending on axle loads and traffic speeds, parameters are established carefully in order to ensure a good quality in terms of geometry and bearing capacity during the entire infrastructure life cycle, preventing deterioration process. Nevertheless, maintenance actions have to be performed aiming to restore proper track condition. The quality control during the construction is an important factor that can evaluate the performance of materials. Nowadays, the materials are mainly characterised by their physical and mechanical properties, but there is an increased interest in developing performance based specifications that can provide more realistic information about the behaviour of the track during the life cycle. In order to achieve this task, non-destructive tests represent a good solution, as they are cost and time efficient. Among non-destructive loading equipment, one of the most efficient is the Falling Weight Deflectometer (FWD). In this research, FWD tests were undertaken during the construction of a new railway line 29 km long, at the top of the substructure and in different months. Based on the performed load tests, the structural modelling of the track was established through back-calculation, and the variation of the materials moduli for different testing campaigns was evaluated. The main results obtained are presented and analysed in this paper, as well as some considerations regarding FWD testing and interpretation.